POSITIVE EFFECTS OF BINAURAL MUSIC ON THE BRAIN - Sumerjana, Ketut; Sudirga, I Komang; Suteja, I Kt.; Suharta, I Wayan (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2024)
Binaural music, which is characterized by the presentation of two slightly different sound frequencies to each ear, has gained increasing attention owing to its potential positive effects on the brain. Research suggests that binaural beats can influence cognitive and emotional states by modulating brainwave activity. When the brain perceives the difference between the two frequencies, it generates a third "perceived" frequency, known as a binaural beat, which corresponds to specific brainwave states (delta, theta, alpha, beta, or gamma). These brainwave states are linked to various mental and physiological benefits, including relaxation, improved focus, enhanced creativity, reduced anxiety, and better sleep quality. Additionally, studies have indicated that regular exposure to binaural beats may promote neuroplasticity, improve memory retention, and facilitate the brain’s capacity for learning and information processing. This abstract provides a concise overview of how binaural music may serve as a tool to improve mental health, cognitive performance, and emotional well-being, offering a promising avenue for therapeutic and wellness applications. Further research is needed to explore the long-term effects and optimal conditions for the impact of binaural music on brain function.